Efektivitas Fermentasi dengan Sumber Substrat yang Berbeda Terhadap Kualitas Jerami Padi - Yusdar Zakaria; Cut Intan Novita; Samadi Samadi (Jurnal Agripet, 2013)
Effectivity of fermentation with different substrates source on rice straw qualityABSTRACT. The research on effectivity of fermentation with different substrates source on rice straw quality has been conducted at Animal Husbandry Field Laboratory, University of Syiah Kuala. The objective of study is to learn rice straw fermented quality as animal feed with addition of different substrat. Complete Randomize Design with factorial pattern consist of two factors which were A = storage time with 2 level ( a1 = one month; a2 = two month) and B = substrate sources (b1 = Coccoa skin fruit, b2 = rice bean and b3 = sagoo). Variables observed were protein level, crude fiber and ash level. The statistical analisis show that there is no significant effect of treatment on protein level, crude fiber and ash. There is no interaction between source of substrates and storage time. These results revealed that all substrates source (coccoa skin fruit, rice bran and sagoo) could used as an energy for starter in rice straw fermented.